Upfront Cranial Radiotherapy vs. EGFR Tyrosine Kinase Inhibitors Alone for the Treatment of Brain Metastases From Non-small-cell Lung Cancer: A Meta-Analysis of 1465 Patients - Du, Xiao-Jing; Pan, Su-Ming; Lai, Shu-Zhen; Xu, Xiao-Nan; Deng, Mei-Ling; Wang, Xiao-Hui; Yao, Dun-Chen; Wu, Shao-Xiong (Frontiers in Oncology, 2018)
Background: Epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) is revolutionizing the management of brain metastases (BMs). This study was to explore the value of upfront cranial radiotherapy (RT) in EGFR-mutated non-small cell lung cancer (NSCLC) with BMs compared with EGFR-TKIs alone. Methods: We searched all topic-related comparative articles in public databases (MEDLINE, EMBASE, Cochrane Library, and Web of Science) and conference proceedings. Outcomes of interest were intracranial objective response rate (ORR), overall survival (OS), and intracranial progression-free survival (PFS). Statistical analyses were calculated using Review Manager 5.3 software. Results: Thirteen comparative studies that included a total of 1,456 patients were eligible. Upfront brain RT had significantly higher OS (HR = 0.78, 95% CI = 0.65–0.93, P = 0.005) than EGFR-TKI alone. Upfront RT plus TKI had superior OS (HR = 0.71, 95% CI = 0.58–0.86, P = 0.0005) and intracranial PFS (HR = 0.69, 95% CI = 0.49–0.99, P = 0.04). The pooled data favored upfront whole brain RT (WBRT) plus TKI in terms of intracranial PFS (HR = 0.64, 95% CI = 0.48–0.85, P = 0.002) and OS (HR = 0.75, 95% CI = 0.57–1, P = 0.05). Upfront stereotactic radiosurgery (SRS) was associated with better OS (HR = 0.37, 95% CI = 0.26–0.54, P < 0.00001). Similar results were observed when analysis was restricted to the use of erlotinib or geftinib. Conclusions: The upfront use of brain RT seemed critical, especially for SRS. Upfront administration of upfront WBRT plus EGFR-TKI had better survival outcomes and seemed superior to EGFR-TKI alone.